PENERAPAN TINDAKAN KEBIRI KIMIAWI BAGI PEDOFIL DALAM PERSPEKTIF HUKUM PERLINDUNGAN ANAK DAN HAK ASASI MANUSIA - Dinda Pratami (2022)
This thesis with the title Application of Chemical Castration for Pedophiles in the Legal Perspective of Child Protection and Human Rights, contains the first, the consequences of the application of chemical castration for pedophiles in the perspective of Child Protection Law and Human Rights. Second the obstacles faced by law enforcers in the application of chemical castration to pedophiles. This research was conducted due to the sharp increase in the number of cases of sexual violence against children, which was aimed at finding the impact of the application and the obstacles in the application of additional punishments of chemical castration. This research uses normative legal research methods, then regarding data analysis techniques using content analysis models, with data collection techniques through library research methods. In analyzing the problem, the researcher uses the theory of legal protection, the theory of law enforcement, the theory of human rights, crime and punishment. The results of this study indicate that the application of the additional punishment of chemical castration, in the view of child protection law, has an impact in the form of a protection for children. And Indonesia's actions which have ratified Law No. 5 of 1998, have a counter impact in the view of Human Rights, which violates Human Rights (HAM) internationally. As well as regarding the obstacles in the implementation process that are felt by law enforcers. First, the absence of further provisions in the chemical castration additional punishment procedure. Second, the uncertainty of the usefulness element in the application of chemical castration additional punishment. Third, the uncertainty of the element of justice in the application of chemical castration additional punishment. Fourth, the lack of expertise regarding chemical castration procedures.